Effect of different parameters on the pDNA-loaded microspheres prepared by double emulsion solvent evaporation method - Doolaanea, Abd. Almonem; Harun Ismail, Ahmad Fahmi; Mohamed, Farahidah (2010)
Biodegradable poly(D,L-lactide-co-glycolide) (PLGA) microspheres is a promising gene carrier system to deliver the gene in gene therapy. This study describes fabrication and characterization of plasmid DNA-loaded PLGA microspheres using a versatile double-emulsion (w/o/w) solvent-evaporation method. For microsphere fabrication, plasmid DNA in TE buffer was added to PLGA solution, previously dissolved in DCM, and was homogenized to form the primary water-in-oil (w/o) emulsion. This w/o emulsion was immediately injected into 1% aqueous PVA and homogenized to form the secondary water-in-oil-in-water (w/o/w) emulsion. The w/o/w emulsion was then transferred to a continuously stirred hardening tank of 1% aqueous PVA and the stirring was continued for 2 hours to allow complete evaporation of DCM. The hardened microspheres were collected by centrifugation, washed and freeze-dried.